A degradable transparent high-barrier film and preparation method thereof
Through the six-layer film structure and precision coating vacuum coating technology, transparent, high-barrier, and degradable packaging films were prepared, solving the problem of difficult degradation of existing environmentally friendly packaging materials in the environment and insufficient barrier performance, and achieving both environmental protection and functionality.
Patent Information
- Application Number
- CN202411547434.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-01
AI Technical Summary
The existing environmentally friendly packaging barrier film materials are difficult to degrade in the environment, causing long-term pollution, and at the same time, their barrier properties and degradability are difficult to take into account.
A transparent high barrier film is prepared by precision coating and vacuum coating technology using a six-layer film structure, including a top coating, an inorganic coating, a pretreatment layer, a base coating, a substrate layer and a heat sealing layer. The film uses degradable substrates such as PLA or PBAT, and improves barrier properties and adhesion through SiOx or AlOx inorganic plating and other platings.
It realizes a transparent, high-barrier, and degradable packaging film, which can biodegrade after being discarded, reduce environmental pollution, and has good transparency and barrier properties.
Smart Images

Figure CN119039648B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of film processing, and in particular to a degradable transparent high-barrier film and a preparation method thereof. Background Art
[0002] The traditional packaging barrier film substrate is generally PET, nylon or BOPP, PE, and the barrier film is made by vacuum coating and coating. Due to the large difference in performance between PET material and PE or PP substrate, it cannot be directly recycled, which is not conducive to environmental protection; if it is discarded into the environment, it will not be completely degraded in 200 to 300 years, which will form white pollution and microplastic pollution, causing deep pollution to the environment; with the introduction of the EU Plastics Convention and the 3060 carbon emission policy, the packaging industry is paying more and more attention to environmental protection issues. The existing environmentally friendly substrates are of a single material type, generally PP or PE substrates, which have poor barrier properties and require coating and coating processing; such materials need to enter the recycling system to be truly environmentally friendly and harmless; if they do not enter the recycling system, they cannot be degraded in the environment and will still cause pollution. Another type of environmentally friendly material is the degradable type, which uses degradable substrates such as PLA or PBAT. However, the pure degradable substrate itself has no barrier properties and requires special plating and coating processes to have high barrier properties. How to better plate and coat the degradable substrate has become the focus and difficulty of the research. Summary of the invention
[0003] The purpose of the present invention is to overcome the above-mentioned defects in the prior art and provide a degradable transparent high-barrier film. The degradable transparent high-barrier film is applied to environmentally friendly packaging bags, has transparent visibility, high barrier function, is degradable, pollution-free throughout the life cycle, decomposable, harmless, and can be degraded and returned to nature after being discarded.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0005] A degradable transparent high-barrier film comprises six layers of film, which sequentially comprise a top coating, an inorganic coating, a pre-treatment layer, a primer layer, a substrate layer, and a heat-sealing layer; the pre-treatment layer comprises one or more of a NiCr coating, a SUS coating, and a Si coating.
[0006] The transparent high-barrier film of the present invention is made of multi-layer stacked films after precision coating and vacuum coating. The product has high transparency, and the state of the contents can be seen clearly and intuitively. It has high barrier properties, can protect the contents from being affected by water vapor or oxygen, and prolong the shelf life of the product; because the coating is SiOx or AlOx, which is an oxide, it can be put into the microwave together with the package to heat, and is very convenient to use in the fields of pre-prepared dishes, etc., and is gradually degraded into water and carbon dioxide plastic materials through the metabolism of microorganisms. Compared with traditional plastic barrier films, biodegradable plastic barrier films have higher environmental protection and sustainability.
[0007] The barrier properties of the film formed by the present invention are as follows: water vapor transmission rate WVTR (Vapor Transmission Rate) ≤ 1g / m2 / day, oxygen transmission rate OTR (Oxygen Transmission Rate) ≤ 1.0cc / m2 / day; light transmittance ≥ 88%, and peeling force between each layer ≥ 2N / 15mm.
[0008] Preferably, the inorganic coating includes one or more of a SiOx coating and an AlOx coating.
[0009] The transparent high barrier film of the present invention is applied to high-end packaging bags, which have high requirements for coating adhesion and interlayer peeling force, generally requiring adhesion ≥ 5B and interlayer peeling force > 2N / 15mm. Therefore, the present invention uses pre-treatment coatings such as NiCr or SUS or Si, the main function of which is to increase the adhesion between the SiOx or AlOx inorganic coating and the substrate, and the interlayer peeling force after composite bag making is significantly improved.
[0010] Preferably, the top coating layer includes one or more of a polyurethane coating and a PVA coating; the bottom coating layer includes one or more of a polyurethane coating and an acrylic coating; the substrate layer includes one or more of a PLA substrate and a PBAT substrate; and the heat-sealing layer includes modified PLA or modified PBAT.
[0011] This product uses PLA or PBAT and other degradable materials as the substrate layer. Due to the poor barrier properties of the degradable substrate, it needs to be matched with a primer layer; a pre-treatment layer, SiOx or AlOx coating; and a top coating; ultimately forming a functional film with high barrier properties to water vapor, oxygen, etc.
[0012] Preferably, the thickness of the top coating layer is 0.1~2um; the thickness of the inorganic coating layer is 10~50nm; the thickness of the pre-treatment layer is 2~15nm; the thickness of the primer layer is 0.1~2um; the thickness of the substrate layer is 15~100um; the thickness of the heat sealing layer is 1~10um, generally 8%~15% of the total thickness.
[0013] Although the present invention adopts a double-layer coating process, the coating thickness is nanometer-level and very thin. For example, the pre-treatment thickness is about 10 nanometers, and the thickness of inorganic coatings such as SiOx or AlOx is about 10-50nm. Transparency can be achieved when the coating is extremely thin. In addition, since the refractive index of the coating is matched with that of the top coating, the coating has a high refractive index and the coating has a low refractive index. The combination has a certain anti-reflection effect, ensuring that the film has a good transparent effect.
[0014] A method for preparing the above-mentioned degradable transparent high-barrier film comprises the following steps:
[0015] A. bonding the heat sealing layer to one side of the substrate layer, and co-extruding and stretching to obtain a substrate layer material with a single-sided heat sealing layer;
[0016] B. coating a primer material on the other side of the substrate layer material of the single-sided adhesive heat-sealing layer, and after curing, forming the primer layer;
[0017] C. Vacuum coating is performed on the primer layer to form the pre-treatment layer;
[0018] D. performing vapor deposition on the pre-treatment layer to form the inorganic coating;
[0019] E. Applying a topcoat material on the inorganic coating, and after curing, performing a aging process to form the topcoat layer, thereby obtaining the degradable transparent high-barrier film.
[0020] The material of the substrate layer is biodegradable materials such as PLA or PBAT, with a thickness of 15~100um; for example, PLA coils are made of starch raw materials from renewable plant resources (such as corn, cassava, etc.). Starch raw materials are saccharified to obtain glucose, which is then fermented with glucose and certain strains to produce high-purity lactic acid, and then polylactic acid particles of a certain molecular weight are synthesized by chemical synthesis. The polylactic acid PLA particles are made into roll films by melt film making and bidirectional (axial and transverse) stretching; after bidirectional stretching, the tensile strength and other mechanical properties and processing properties of the substrate are improved; this material is degraded into carbon dioxide and water by 90% in about 180 days under composting conditions, at a temperature above 55°C or under the action of oxygen and microorganisms, realizing the material cycle in nature, and will not affect the environment. It is an ideal green polymer material.
[0021] Preferably, in step C, the vacuum coating operation includes: in a vacuum chamber, high corona first excites plasma, and then uses plasma to excite the surface molecules of the target material to combine with the base coating, thereby generating an anchoring effect on the organic and inorganic interface to form the pretreatment layer.
[0022] The pretreatment layer is a coating of NiCr, SUS or Si with a thickness of 2 to 15 nm, which increases the adhesion between the SiOx or AlOx coating and the base coating. The pretreatment layer is formed in a vacuum chamber by high corona to excite plasma, and then the plasma is used to excite the surface molecules of the NiCr or SUS or Si target to combine with the coating surface, forming an anchoring effect on the organic and inorganic interface.
[0023] Preferably, in step D, the vapor deposition includes one or more of physical vapor deposition and chemical vapor deposition.
[0024] The inorganic coating is SiOx or AlOx, with a thickness of 10~50nm. It uses the physical microscopic density of SiOx and AlOx and the unsaturated bonds of the molecules to adsorb gas molecules to form a good gas barrier performance. It is a functional layer with excellent barrier properties for water vapor and oxygen, and has high transparency. The coating is a non-metallic layer, which can be heated by microwaves and can be detected by metal detection. The coating is prepared by PVD (physical vapor deposition) or CVD (chemical vapor deposition) process. The PVD processing method is: in a high vacuum chamber, the air pressure is ≤4.0x10-4mbar, and high-energy electron beam thermal evaporation or crucible heating evaporation is used. The method of forming a nano-SiOx or AlOx coating is to form a plasma under high voltage, and bombard the Si target or Al target under the action of a controlled electromagnetic field, and react with the introduced process gas O2 to form SiOx or AlOx deposited on the surface of the base coating to form a dense nano-coating; the SiOx layer can also be deposited by CVD (chemical vapor deposition), using gas glow discharge to ionize the rarefied gas under a high-frequency electric field to generate plasma, in which the raw material gas silane (SiH4) is thermally decomposed on the substrate surface in an oxygen-containing atmosphere, and reacts with oxygen to form dense SiOx. The reaction deposition temperature is generally 200℃~400℃.
[0025] Preferably, in step B, the coating includes one or more of gravure coating and narrow slit coating; and the curing includes one or more of thermal curing and UV curing.
[0026] The primer layer has a thickness of 0.1~2um, which increases the adhesion between the coating and degradable substrates such as PLA or PBAT. The primer layer is a polyurethane or acrylic coating. The polyurethane or acrylic coating is evenly coated on the surface of PLA or PBAT by gravure or narrow slit coating. The coating is treated by heat baking or UV curing process to make the internal polymer of the coating cross-linked and finally solidified on the surface of the substrate.
[0027] Preferably, in step E, the coating includes one or more of gravure coating and narrow slot coating; and the curing includes one or more of thermal curing and UV curing.
[0028] Preferably, in step E, the temperature of the aging process is 40-60° C.; and the time of the aging process is 48-120 hours.
[0029] The topcoat also has the function of blocking water vapor and oxygen, while protecting the SiOx or AlOx coating, with a thickness of 0.1~2um; use coatings such as polyurethane or PVA (polyvinyl alcohol) to evenly coat the polyurethane or acrylic coating on the surface of biodegradable substrates such as PLA or PBAT through gravure or narrow slit coating. The coating is treated by heat baking or UV curing process to allow cross-linking reaction inside the coating and finally solidify on the surface of the substrate. After the coating process is completed, a 40~60℃x48H~120H aging process is used to make the polymer reaction cross-linking of the coating more complete and stable.
[0030] Heat sealing layer is used for heat sealing in the packaging process. The heat sealing layer uses modified PLA or modified PBAT. The melting point of modified PLA or PBAT is lower than that of ordinary PLA or PBAT. The thickness is about 8%~15% of the total thickness. It is heat-sealed and formed under the conditions of 85℃, 0.1Mpa, 0.5~3S, and the heat sealing strength can reach more than 2.5N / 15mm.
[0031] The implementation of the present invention has the following beneficial effects:
[0032] The barrier film and heat-sealed bags made by plating and coating PLA or PBAT substrates are biodegradable, reducing carbon footprint, and complying with global environmental policy trends; they have excellent barrier properties, protecting the contents from water vapor or oxygen; they have good transparency, and the state of the contents can be clearly seen; since the barrier layer is SiOx or AlOx non-metallic, which is an oxide, it can be heated by microwaves; it is also convenient to scan and detect whether there is metal residue in the packaging bag. Biodegradable plastics are very environmentally friendly. Once this material comes into contact with the soil, it will begin the process of biodegradation. It can be naturally degraded in landfills. Biodegradable plastics will not have any impact on solid waste collection and recycling systems, and can also reduce related collection costs.
[0033] The present invention particularly uses biodegradable biaxially oriented PLA or PBAT substrates, and manufactures transparent high-barrier films through vacuum coating and coating processes; it takes into account both the functionality of the packaging and the degradable environmental protection, and through the coating (SiOx or AlOx) coating process, the material has high barrier properties, protecting the contents from being damaged by oxygen, water vapor, etc. At the same time, since the coating material of the coating (SiOx or AlOx) is transparent, the packaging can be transparent, making the contents of the packaging clearly visible. Since the barrier layer is SiOx or AlOx non-metal, which is an oxide, it can be heated by microwaves; it is also convenient to scan and detect whether there is metal residue in the packaging bag. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is a schematic diagram of the structure of the degradable transparent high-barrier film of the present invention. DETAILED DESCRIPTION
[0035] Example 1
[0036] like Figure 1 As shown, a degradable transparent high-barrier film includes six layers of film, which include a top coating, an inorganic coating, a pretreatment layer, a primer layer, a substrate layer, and a heat-sealing layer in sequence.
[0037] The preparation method comprises the following steps:
[0038] A. bonding a heat-sealing layer on one side of the substrate layer, and co-extruding and stretching to obtain a substrate layer material with a single-sided heat-sealing layer;
[0039] B. Applying a primer material on the other side of the substrate layer material with a single-sided heat-sealing layer, and after curing, forming a primer layer;
[0040] C. Vacuum coating is performed on the base coating to form a pre-treatment layer;
[0041] D. Performing vapor deposition on the pre-treatment layer to form an inorganic coating;
[0042] E. Apply a topcoat material on the inorganic coating, and after curing, perform a aging process at 45° C. for 72 hours to form a topcoat to obtain a degradable transparent high-barrier film.
[0043] In this embodiment, the top coating is 1um thick polyurethane, the inorganic coating is 30nm thick AlOx, the pretreatment layer is 10nm thick NiCr coating, the primer layer is 1um thick acrylic coating, the substrate layer is 40um thick PLA, and the heat sealing layer is 4um thick modified PLA.
[0044] Example 2
[0045] like Figure 1 As shown, a degradable transparent high-barrier film includes six layers of film, which include a top coating, an inorganic coating, a pretreatment layer, a primer layer, a substrate layer, and a heat-sealing layer in sequence.
[0046] The preparation method comprises the following steps:
[0047] A. bonding a heat-sealing layer on one side of the substrate layer, and co-extruding and stretching to obtain a substrate layer material with a single-sided heat-sealing layer;
[0048] B. Applying a primer material on the other side of the substrate layer material with a single-sided heat-sealing layer, and after curing, forming a primer layer;
[0049] C. Vacuum coating is performed on the base coating to form a pre-treatment layer;
[0050] D. Performing vapor deposition on the pre-treatment layer to form an inorganic coating;
[0051] E. Apply a topcoat material on the inorganic coating, and after curing, perform a aging process at 40° C. for 120 hours to form a topcoat layer to obtain a degradable transparent high-barrier film.
[0052] In this embodiment, the top coating is 2um thick PVA, the inorganic coating is 50nm thick SiOx, the pretreatment layer is 15nm thick SUS coating, the primer layer is 2um thick polyurethane coating, the substrate layer is 100um thick PBAT, and the heat sealing layer is 10um thick modified PBAT.
[0053] Example 3
[0054] like Figure 1 As shown, a degradable transparent high-barrier film includes six layers of film, which include a top coating, an inorganic coating, a pretreatment layer, a primer layer, a substrate layer, and a heat-sealing layer in sequence.
[0055] The preparation method comprises the following steps:
[0056] A. bonding a heat-sealing layer on one side of the substrate layer, and co-extruding and stretching to obtain a substrate layer material with a single-sided heat-sealing layer;
[0057] B. Applying a primer material on the other side of the substrate layer material with a single-sided heat-sealing layer, and after curing, forming a primer layer;
[0058] C. Vacuum coating is performed on the base coating to form a pre-treatment layer;
[0059] D. Performing vapor deposition on the pre-treatment layer to form an inorganic coating;
[0060] E. Apply a topcoat material on the inorganic coating, and after curing, perform a aging process at 60° C. for 48 hours to form a topcoat to obtain a degradable transparent high-barrier film.
[0061] In this embodiment, the top coating is 0.1um thick polyurethane, the inorganic coating is 10nm thick SiOx, the pretreatment layer is 2nm thick Si coating, the primer layer is 0.1um thick polyurethane coating, the substrate layer is 15um thick PLA, and the heat sealing layer is 1um thick modified PLA.
[0062] Comparative Example 1
[0063] The materials and process are selected as in Example 1, except that step D is omitted and other steps remain unchanged, so as to prepare a five-layer barrier film without an inorganic coating.
[0064] Comparative Example 2
[0065] The materials and process are selected as in Example 1, except that step C is omitted and the other steps remain unchanged, that is, a five-layer barrier film without a pre-treatment layer is prepared.
[0066] Comparative Example 3
[0067] The materials and process are the same as those in Example 2, except that step C is omitted and the other steps remain unchanged, so that a five-layer barrier film without a pre-treatment layer is prepared.
[0068] Effect Example 1
[0069] The barrier films prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to performance tests, and the test methods or instruments for each index were as follows:
[0070] Light transmittance: ASTM D1003. Specifically: Use a spectrophotometer to test the light transmittance of the barrier film material at room temperature (23±2℃).
[0071] Appearance color: visual inspection. Specifically: at room temperature (23±2℃), under fluorescent light, 30-40cm away from the film surface, visually observe to evaluate whether the substrate is transparent.
[0072] Initial water permeability WVTR: ASTM F1249 MOCON. Specifically: Use a sampler to cut a sample of the barrier film, put it into a professional water vapor transmission rate tester, set the tester to 38℃ and 90% relative humidity for measurement, and test the amount of water vapor permeated per square meter of the barrier film per day. The unit is g / m2 / day.
[0073] Initial oxygen permeability OTR: ASTM D3985 MOCON. Specifically: Cut the barrier film sample with a sampler, put it into a professional oxygen permeability tester, set the relative humidity at 23℃ and 0% in the tester, and test the amount of oxygen permeated per square meter of barrier film per day. The unit is cc / m2 / day.
[0074] Initial adhesion: ASTM D3359-09. Specifically: use a grid knife to draw a grid pattern on the barrier film, use 3M610 tape to stick to the coating surface, pull the tape apart, and evaluate the coating and plating shedding area. If there is no shedding, the adhesion is 5B, if the shedding area is less than 5%, it is 4B, if the shedding area is between 5% and 15%, it is 3B, if the shedding area is between 15% and 35%, it is 2B, if the shedding area is between 35% and 65%, it is 2B, and if the shedding area is greater than 65%, it is 0B.
[0075] Interlayer peeling force after compounding: GB / T8808-88. Specifically: at room temperature (23±2℃), use the two ends of the electronic tensile tester to clamp the two layers of the composite sample at 180°, at a speed of 30mm / min; the electronic tensile tester automatically records the average tensile force, which is the peeling force.
[0076] The test design is shown in Table 1:
[0077] Table 1
[0078]
[0079] Among them, the barrier film is a film that has barrier properties to water vapor and oxygen. The better the barrier performance, the lower the water vapor transmission rate (WVTR) and oxygen transmission rate (OTR).
[0080] From the test results, it can be seen that if only NiCr or SUS layer is plated, there is good adhesion and interlayer peeling strength after composite, but the sample has basically no barrier performance after coating; if only SiOx or AlOx layer is plated, there is only barrier property and poor adhesion. Only by using the scheme of the present invention to simultaneously plate NiCr / SUS+SiOx or NiCr / SUS+AlOx layers can adhesion, interlayer peeling strength and barrier properties be achieved at the same time.
[0081] The above disclosure is only a preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.
Claims
1. A degradable transparent high barrier film, characterized in that: The six-layer film includes a top coating, an inorganic coating, a pre-treatment layer, a primer layer, a substrate layer, and a heat-sealing layer in sequence; the pre-treatment layer includes one or more of a SUS coating and a Si coating; the inorganic coating includes one or more of a SiOx coating and an AlOx coating; The preparation of the degradable transparent high-barrier film comprises the following steps: A. bonding the heat sealing layer to one side of the substrate layer, and co-extruding and stretching to obtain a substrate layer material with a single-sided heat sealing layer; B. coating a primer material on the other side of the substrate layer material of the single-sided adhesive heat-sealing layer, and after curing, forming the primer layer; C. Vacuum coating is performed on the primer layer to form the pre-treatment layer; D. performing vapor deposition on the pre-treatment layer to form the inorganic coating; E. Applying a topcoat material on the inorganic coating, curing it, and then performing a aging process to form the topcoat; The degradable transparent high-barrier film is obtained.
2. The degradable transparent high-barrier film according to claim 1, characterized in that: The top coating layer includes one or more of a polyurethane coating and a PVA coating; the bottom coating layer includes one or more of a polyurethane coating and an acrylic coating; the substrate layer includes one or more of a PLA substrate and a PBAT substrate; and the heat sealing layer includes one or more of a modified PLA and a modified PBAT.
3. The degradable transparent high-barrier film according to claim 1, characterized in that: The thickness of the top coating is 0.1-2um; the thickness of the inorganic coating is 10-50nm; the thickness of the pretreatment layer is 2-15nm; the thickness of the primer layer is 0.1-2um; the thickness of the substrate layer is 15-100um; and the thickness of the heat sealing layer is 1-10um.
4. A method for preparing the degradable transparent high-barrier film according to claim 1, characterized in that: The steps include: A. bonding the heat sealing layer to one side of the substrate layer, and co-extruding and stretching to obtain a substrate layer material with a single-sided heat sealing layer; B. coating a primer material on the other side of the substrate layer material of the single-sided adhesive heat-sealing layer, and after curing, forming the primer layer; C. Vacuum coating is performed on the primer layer to form the pre-treatment layer; D. performing vapor deposition on the pre-treatment layer to form the inorganic coating; E. Applying a topcoat material on the inorganic coating, curing it, and then performing a aging process to form the topcoat; The degradable transparent high-barrier film is obtained.
5. The method for preparing the degradable transparent high-barrier film according to claim 4, characterized in that: In step C, the vacuum coating operation includes: in a vacuum chamber, high corona first excites plasma, and then uses plasma to excite the surface molecules of the target material to combine with the base coating, thereby generating an anchoring effect on the organic and inorganic interface to form the pretreatment layer.
6. The method for preparing the degradable transparent high-barrier film according to claim 4, characterized in that: In step D, the vapor deposition includes one or more of physical vapor deposition and chemical vapor deposition.
7. The method for preparing the degradable transparent high-barrier film according to claim 4, characterized in that: In step B, the coating includes one or more of gravure coating and narrow slit coating; the curing includes one or more of thermal curing and UV curing.
8. The method for preparing the degradable transparent high-barrier film according to claim 4, characterized in that: In step E, the coating includes one or more of gravure coating and narrow slit coating; the curing includes one or more of thermal curing and UV curing.
9. The method for preparing the degradable transparent high-barrier film according to claim 4, characterized in that: In step E, the temperature of the aging process is 40-60° C.; the time of the aging process is 48-120 hours.
Citation Information
Patent Citations
Easily-recycled transparent high-barrier film
CN221272208U
High-barrier, biodegradable resin film
JP2006327003A